Crossplay: a liberdade da fluidez de gênero em minhas práticas de cosplay - OLIVEIRA, Erika Fiore de (2022)
The present essay was created on the perspective over my cosplay practices, traced in a chronological timeline. Thus, I identify the construction of my gender identity, flowing between sexes and points towards a deconstruction of the rigid notion of gender function in the Crossplay practice. The accomplishment of this essay had its theory basis on the concept of Microscopic Transexuality by Gillles Deleuze and Felix Guattari.